Construction of a recombinant eukaryotic expression vector containing a leptin gene and its expression in HPMSCs - Jin, Julou (Springer Netherlands, 2013)
Leptin gene fragments were amplified from human adipose tissue using reverse transcription polymerase chain reaction technology. The leptin gene was reconstructed in pIRES2-EGFP and transfected into human placenta-derived mesenchymal stem cells (HPMSCs) using a liposome-mediated method. Leptin mRNA and protein was detected in the transfected cells using RT-PCR and Western blot analysis, and the results showed that HPMSCs transfected with pIRES2-EGFP-leptin expressed significantly more leptin mRNA and protein than HPMSCs transfected with pIRES2-EGFP. EGFP expression was observed under a fluorescence microscope, and results showed the report gene to have been successfully transferred into the target cells. The biological activity of leptin and the cell proliferation activity of HPMSCs transfected with pIRES2-EGFP-leptin was detected using an MTT assay, which showed that leptin can promote the proliferation of HPMSCs. However, leptin in HPMSCs transfected with pIRES2-EGFP-leptin showed significantly more activity than HPMSCs transfected with pIRES2-EGFP. Identification of multipotency showed that HPMSCs transfected with pIRES2-EGFP-leptin maintained their multipotency.